Winged bean chymotrypsin inhibitors retard growth of Helicoverpla anmigera - Telang, Manasi A.; Giri, Ashok P.; Pyati, Prashant S.; Gupta, Vidya S.; Tegeder, Mechthild; Franceschi, Vincent R. (Gene, 2009)
Two putative Kunitz-type chymotrypsin inhibitor genes (WC12 and WC15) were isolated from winged bean (Psophocarpus tetragonolobus (L.) DC). While WC12 has previously been characterized, WC15 represents a new member of the WC1 family. WC15 was exclusively expressed in winged bean seeds. Theoretical translation of both the genes resulted into polypeptides of 207 amino acids with 86% sequence similarity. The polypeptide sequences contain four half-cysteine residues and a well-conserved Leu(65)-Ser(66) reactive site, typical for chymotrypsin inhibitors. WC15 and WC12 were expressed in Pichia pastoris and the recombinant proteins were assayed against various proteinases. Both the inhibitors strongly inhibited commercially available bovine chymotrypsin. More importantly, gut proteinases of Helicoverpa armigera larvae that damage many important crop plants, were inhibited by WC12 and WC15. In addition, both proteinase inhibitors demonstrated significant reduction of growth of H. armigera larvae after feeding on inhibitor incorporated artificial diets. The inhibitory effects of WC12 and WC15 on activity of proteinases and larval growth make these proteins and their genes promising candidates for enhancing plant defense against H. armigera using transgenic plants. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Antimetabolic effect; Digestive gut proteinases; Kunitz-type proteinase inhibitor; Organ-specific mRNA expression; Psophocarpus tetragonolobus